THE REEATIONSHIP BETWEEN AFFECTIVE AND OTHER PSYCHIATRIC DISORDER WITH CREATIVE ACTIVITY AND SOME OF THEIR NEUROCHEMICAE MECHANISMS - Bedlinskyi, V.O. (The Ukrainian Scientific Medical Youth Journal, 2017)
The article is based on the study for the relationship between affective and other psychiatric disorders with the creative activity of an individual. The historical and contemporary views on this problem were analyzed, considering modern data on neurochemical mechanisms, which play a big role in the process of creativity, and in the development of mental illness. The role of dopaminergic neurotransmission as one of the main biochemical mechanisms of providing creative ability was highlighted. It was concluded that studying and taking into account the relationship between psychiatric disorders and creative activity, including the role and features of the functioning of neurotransmitter systems, can serve as a means of improving the treatment-diagnostic, preventive and reabilitation care of this category of mentally ill.